Investigation on solubilisation behaviour of l-isoleucine polymorph and its associated thermodynamics properties / Vannessa Shallomy Darrell - Darrell, Vannessa Shallomy (2024)
The motivation to determine the relationship of thermodynamic behaviour (solubilities) and properties between L-isoleucine polymorphic forms grown in water and to understand the molecular interaction behaviour between the solute-solvent molecules at the molecular level between L-isoleucine and water has been the reasons to establish this work. To achieve these objectives, the study of physico-chemical properties of Lisoleucine was carried out, i.e., through (1) isothermal and polythermal dissolution methods, (2) solid-state properties determination, and (3) molecular modelling for solubilisation prediction. The L-isoleucine polymorphic forms were recrystallised using isothermal and polythermal crystallisation techniques. The product crystals were analysed by means of x-ray powder diffraction, differential scanning calorimetry, fourier transform infrared, and an optical microscope to evaluate the form produced. The dried L-isoleucine crystals were then used as the feed for solubility determination experiments.